The effect of physical fitness and physical activity level on memory storage of Italian pre-adolescent secondary school students - Russo, Gabriele; Nigro, Federico; Raiola, Gaetano; Ceciliani, Andrea (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Physical activity could enhance some psychological functions, and it is crucial for the growth of individuals. Aim of Study. The present investigation aimed at testing preadolescent students’ memory functions to understand whether physical activity and physical fitness can increase memory storage. Material and Methods. A battery of physical tests (MOTORFIT) and questionnaire (PAQ-C, RSES – self-esteem) were administered to identify the physical and psychological characteristic of the students. A Free Recall Memory Test was performed by the children in order to assess their memory skills. In the memory test, participants had to memorize as many words as possible from a list of 20 words presented. Participants had to write down as many words as possible in two different times, 100 seconds after the presentation (e.g., immediate recall) of the 20 words and after 12 minutes (e.g., delayed recall). Results. The results showed an effect of physical fitness but did not show an effect of physical activity level. In particular, results highlight that students with high physical fitness are able to remember more words than pre-adolescent with low physical fitness. Conclusions. Our results provide evidence that physical practice could lead to an enhancement of memory functions.
Keywords: schoolchildren; physical education; delayed recall; immediate recall; reactivation stage